Cover Image, Volume 33, Issue 4. Issue 4 (23rd March 2023) - Kempermann, Gerd; Song, Hongjun; Gage, Fred H.
Abstract : The cover image is based on the Editorial Adult neurogenesis in the hippocampus by Gerd Kempermann et al., https://doi.org/10.1002/hipo.23525 .